The effect of instruction designed with integral ASIE model on learning of genetics of preservice science teachers - ORHAN, Sema İrem; AYDIN, Abdullah (Elementary Education Online, 2020)
This study aims to examine the effect of the use of activities designed by the Integral ASIE Model to learning about genetics in third grade genetics and biotechnology class of preservice science teachers and to determine the opinions of preservice teachers regarding this model and implementation period. The research was conducted with the participation of 39 preservice teachers studying at third grades of the Department of Science Education, Faculty of Education at a State University in the spring semester of 2016-2017 education year. While the activities organized with the Integral ASEI Model were utilized for the preservice teachers included in the experimental group about learning genetics; the control group was explained about the project in line with the current science curriculum. According to the findings, it was concluded that the education designed according to Integral ASIE model in genetics had an effect on enhancing the academic achievement of science preservice teachers in terms of genetics. The content analysis of data obtained from semi-structured interviews applied to the preservice teachers in the experimental group support this result.
Keywords: 4. Education